Seizure signal analysis using spectogram / Aqilah Abdul Samad - Abdul Samad, Aqilah (2014)
Electroencephalogram (EEG) is a technique that records the brain electrical activity. This technique is widely used by neurologist to study human brain functions and lead them to investigate a disorder related to brain such as epilepsy, tumor and seizure. The output of EEG signals is in microvolts (μV) and its characteristics are very non-linear, non-stationary and very weak; it can be easily contaminated by other sources. Furthermore, by using visual inspection method, it is quite difficult to extract useful information from these signals just by observation. Thus, to overcome the limitation of the visual inspection method, the time-frequency analysis using Spectrogram method has been applied to analyze seizure from EEG signal test. This method has the ability to extract weak signal that are non-linear, nonstationary such as EEG signal. Spectrogram yields an output of power at each frequency of the EEG signal as a function of time. This method portrait the relationship between power density and frequency respective to time and it is used to extract the hidden information in EEG signal. In this research, the results of the Spectrogram showed that a dominant frequency of a healthy subject signal is in the range of 7.5 Hz to 13 Hz and for seizure subject the signal is from 1 Hz to 3 Hz. The statistical analysis justified that the findings of seizure onset signal has a dominant frequency in range of delta rhythm and the healthy subject signal has dominant frequency in range of alpha rhythm.